Analisis Perbandingan Estimasi Cadangan Hidrokarbon Berdasarkan Simulasi Reservoir CMG dan Decline Curve Analysis - Setyawan, Wildan; Alriski, Alriski; Nuraliyah, Zahrah (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Hydrocarbon reserve estimation is a fundamental aspect in oil and gas field development planning and project economic evaluation. This study compares two reserve estimation approaches: reservoir simulation using Computer Modelling Group (CMG) and Decline Curve Analysis (DCA) with Microsoft Excel. CMG simulation uses IMEX module to model conventional reservoir with Original Oil in Place (OOIP) of 1.9735 × 10⁷ STB. DCA method analyzes three production decline models with initial production rate parameter of 1,065 BOPD and decline rate of 50% per year. Results show different 36-month cumulative production predictions: Exponential decline yields 172 MBO, Hyperbolic decline 212 MBO, and Harmonic decline 241 MBO with difference reaching 40%. Hyperbolic decline method provides optimal balance for heterogeneous reservoir characteristics. Combination of both approaches provides strong cross-validation for more accurate reserve estimation in supporting field development decision making.